The Reasons for the Weakness of Students of the Classroom Teacher Major in the Tafila Technical University in the Recitation and Tajweed Skill from their Point of View - Shadi Fakhri Abo Latifa; Abd Kareem Mahmood Al-Salaheen (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The objective of the study is to identify the reasons behind the weakness of students in the Tafila Technical University in the Recitation and Tajweed skill from their point of view. Both researchers adopted the descriptive survey.  The study samples consisted of  90 female students from  the classroom teacher major in Tafila Technical University in the second semester of the academic year 2018/2019. To achieve the study objectives, researchers developed a survey containing 26 articles focused on two main section. The first is about the basic data of the study individuals while the second is the reasons for the weakness of students of the classroom teacher major in the Tafila Technical University in the Recitation and Tajweed skill from their point of view, which branches into three areas: Student related, tutor related & tutoring method related. The most important results of the study are the calculated average of the study sample response for the reasons for the weakness of students of the classroom teacher major in the Tafila Technical University in the Recitation and Tajweed skill from their point of view came quite high on a general level. Among the recommendation of the study was to have lectures to make the students aware of the importance of recital & Tajweed skills.